The practice of operations research in Malaysia and Singapore - Kwong, Han Chun (Elsevier, 1986)
This paper examines various aspects of the use of computer-based operations research (OR) in organisations in Malaysia and Singapore. It discusses the extent of adoption of OR techniques, the frequency of use, the types of management decision on which the techniques are deployed and the functional areas using them. The extent to which computer availability has encouraged the use of OR, and the hardware and software support in the implementation of OR are considered. Also, the characteristics of the OR practitioners, implementation difficulties encountered and the management user's perception of the usefulness of OR techniques are studied. Further, reasons for nonusage and the prospects for OR in Malaysia and Singapore are explored. Finally, directions for further research that have not previously been raised are suggested. In general, the patterns of OR usage in these newly industrialising countries of south-east Asia are dissimilar to those in the developed countries. © 1986.